Heterogeneous Motivations of Household - Level Coca Growing Areas: The Case of an Indigenous Community in Peru - Jaqueline Garcίa-Yi (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
There is a great deal of heterogeneity among coca growers in Peru, a fact that the national organizations and international co-operation have recognized, but has not been able to address property in anti-drug policy design. In this paper, we investigate the joint decision to grow coca and the decision of the quantity of coca bushes to cultivate, first under a homogeneity assumption, and then relaxing this assumption to allow for heterogeneity. Our research results support the notion of coca grower heterogeneity, identify the differences between groups of coca growers, and suggest different anti-drug policies, based on their effects in each group.
Keywords: 330; coca; heterogenous; latent class; cragg model; Peru